The Role of Ionic Liquids in Performance Enhancement of Two‐Step Perovskite Photovoltaics. Issue 1 (2nd January 2023) - Liang, Xiao; Duan, Dawei; Al-Handawi, Marieh B.; Wang, Fei; Zhou, Xianfang; Ge, Chuang-ye; Lin, Haoran; Zhu, Quanyao; Li, Liang; Naumov, Panče; Hu, Hanlin
Abstract : Ionic Liquids‐Assisted Perovskites In article number 2200856, Quanyao Zhu, Liang Li, Pancˇe Naumov, Hanlin Hu, and co‐workers introduced ionic liquids MAAc into the PbI2 layer by a sequential deposition process. They found that the addition of MAAc has lowered the perovskite formation enthalpy and suppressed the trap state density, delivering a champion device with a power conversion efficiency of 23.36% with significantly improved durability.